“Feedback is communication between human beings”: understanding adolescents' conception of written qualitative feedback - Sining Tao; Wenjuan Qin (Frontiers in Language Sciences)
Research on feedback in writing has predominantly focused on its effectiveness in improving surface-level linguistic accuracy, with limited attention to how students perceive and engage with written qualitative feedback as an interactive tool for writing development. This study addresses this gap by emphasizing the role of written qualitative feedback, defined as descriptive comments that address both content and linguistic element, promoting deeper engagement and critical thinking in student writing. Using an explanatory sequential mixed-methods design, the study examines the conception of written qualitative feedback held by 107 English as a Foreign Language (EFL) learners in China. Over an academic semester, each learner produced three argumentative texts and received written qualitative feedback in three formats. Quantitative data from an adapted Conception of Written Feedback questionnaire reveals two predominant patterns in their conception of written qualitative feedback: (1) engaging with positive emotion and active use or (2) ignoring with defensiveness. To explore potential explanations for these patterns, a purposeful subsample of 10 learners participated in semi-structured interviews, conceptualizing the role of feedback in their writing practices. Qualitative findings indicate that learners perceive feedback along a continuum as an instructional tool, evaluative system, cognitive guide, dialogic conversation, and catalyst for personal change. By triangulating quantitative results and qualitative findings, the study demonstrates how personalized educational interaction in the form of written qualitative feedback facilitates adolescents' transition from competent language use to higher-order argumentative skills and agentic approaches to writing development. The study adds to a growing literature on adolescent writing development from the lens of interactive teaching and learning.